Crystal Alignment Technology of Electrode Material for Enhancing Electrochemical Performance in Lithium Ion Battery. Issue 4 (1st April 2021) - Kim, Cham; Yang, Yeokyung; Lopez, David Humberto
Abstract : The crystal alignment technology of lithium nickel manganese oxide (LiNi0.5 Mn0.3 Co0.2 O2 ) is proposed using its magnetic properties. The crystalline LiNi0.5 Mn0.3 Co0.2 O2 exhibits the paramagnetic behavior at room temperature as well as the magnetic anisotropy originated from its crystallographic anisotropy. If the crystalline LiNi0.5 Mn0.3 Co0.2 O2 is exposed to a magnetic field, it can tend to rotate to an angle minimizing its system energy due to spontaneous magnetization. Taking these magnetic natures into account, the vector quantity of an external magnetic field (i.e., magnetic flux density and field direction) is adjusted to apply to a viscous LiNi0.5 Mn0.3 Co0.2 O2 slurry coated onto a current collector; thus, the crystal aligned LiNi0.5 Mn0.3 Co0.2 O2 electrode is obtained, in which the (00 l ) plane is notably oriented perpendicular to the surface of a current collector. The aligned LiNi0.5 Mn0.3 Co0.2 O2 electrode consistently records superior electrochemical performance to a pristine LiNi0.5 Mn0.3 Co0.2 O2 electrode because the former demonstrates an improved capability of lithium ion transport during the charge/discharge process in a lithium ion battery. The aligned LiNi0.5 Mn0.3 Co0.2 O2 is considered to have the improved transport capability because the kinetics of lithium ion transport in LiNi x Mn y Co1-( x + y ) O2 intrinsically occurs along the (00 l ) plane.